Chimarrão consumption and prognostic factors in breast cancer: Correlation with antioxidants and blood caffeine levels. (14th September 2020) - Calixto, Maria Rachel Pedrazzoli; Rech, Daniel; dos Santos, Vanessa L.; Madeira, Tiago Bervelieri; Nixdorf, Suzana Lucy; Fagundes, Tatiane Renata; Davis, Rachel Ann Hauser; Bastos, Frederico Freire; Bastos‐Neto, Jayme da Cunha; Bastos, Vera Lucia Freire da Cunha; Zanandrea, Ana Carolina; de Lima, Josivan Ribeiro; et al.
Abstract : Breast cancer is the second most common malignancy among women. Ilex paraguariensis A. St. Hil, known as yerba mate, is widely consumed in southern Brazil as a hot infusion drink known as chimarrão. This herb has a complex chemical composition and is rich in antioxidants, which may interfere in the course of chronic inflammatory diseases as breast cancer. This study investigated the impact of chimarrão consumption on the clinicopathological profile of women with breast cancer attended at Francisco Beltrão Cancer Hospital, Paraná, Brazil. Blood antioxidants and caffeine profiles were assessed. Decreases in reduced glutathione and metallothionein levels, and increase in catalase activity were observed among breast cancer patients that were chimarrão consumers. The levels of circulating caffeine in breast cancer patients with luminal A tumors were higher than those in patients with luminal B and HER‐2 subtypes. Furthermore, overweight patients presented higher caffeine levels than the eutrophic ones. It was found positive associations between chimarrão intake and high body mass index, and chimarrão intake and menopause at diagnosis. Altogether, these findings suggest that chimarrão consumption affects the blood antioxidants of breast cancer patients, and that the caffeine present in this mixture may favor the development of tumor of good prognosis. Highlights: Chimarrão consumption may affect the course of chronic inflammatory diseases, as breast cancer. Chimarrão intake changed blood antioxidants in breast cancer patients who were current consumers when compared to the non‐consumers ones. High levels of caffeine were detected in patients bearing luminal A tumors, suggesting a protective role. Highlights: Chimarrão consumption may affect the course of chronic inflammatory diseases, as breast cancer. Chimarrão intake changed blood antioxidants in breast cancer patients who were current consumers when compared to the non‐consumers ones. High levels of caffeine were detected in patients bearing luminal A tumors, suggesting a protective role.